Effect of reactive silica sources on the properties of Na-metakaolin-based geopolymer binder. (18th January 2023) - Bezerra, B.P.; Morelli, M.R.; Luz, A.P.
Highlights: Colloidal silica combined with NaOH resulted in a very reactive activating solution. The NaOH-CS activator enhanced the mechanical and thermal stability of MK-geopolymer. GP-CS exhibited good thermal stability and suitable CCS after firing at 1000 °C. The crystallization of mullite at 1000 °C enhanced the mechanical strength of GP-CS. Abstract: Geopolymer has been pointed out as a potential sustainable material for applications with distinct complexities. Regarding the synthesis and processing of such materials, there are still some technical challenges associated with the particularities of the selected raw materials. This work investigated the role of reactive silica sources on the setting time, physical and mechanical properties of Na-metakaolin-based geopolymer binder. In this sense, different activating solutions (AS) were analyzed containing plain NaOH or NaOH combined with sodium silicate, or silica fume, or colloidal silica. The setting behavior, cold crushing strength and elastic modulus evolution as a function of time (up to 16 days) of the designed formulations were measured after curing the prepared samples at 40 °C for 24 h. The most promising compositions were then fully characterized and had their properties evaluated after thermal treatments in the 200 to 1000 °C temperature range. The results indicated that the best performance was obtained for the geopolymer containing colloidal silica (GP-CS) in its activating solution. Such binder also exhibited fast setting, good thermal stability, suitable cold crushing strength (7.1 MPa) and low porosity (2.3%) after firing the samples at 1000 °C. FTIR and DRX profiles of GP-CS highlighted the generation of a high number of Si-O-Al bonds, which induced the crystallization of mullite phase at 1000 °C and enhanced the mechanical strength of this geopolymer. Thus, the use of colloidal silica suspension to design novel activating solutions is an interesting route to prepare geopolymers with improved performance and thermal stability.